Further supporting evidence for the SATB2‐associated syndrome found through whole exome sequencing. (May 2015) - Zarate, Yuri A.; Perry, Hazel; Ben‐Omran, Tawfeg; Sellars, Elizabeth A.; Stein, Quinn; Almureikhi, Mariam; Simmons, Kirk; Klein, Ophir; Fish, Jennifer; Feingold, Murray; Douglas, Jessica; Kruer, Michael C.; et al.
<x xml:space="preserve">Abstract</x> The SATB2‐associated syndrome (SAS) was recently proposed as a clinically recognizable syndrome that results from deleterious alterations of the SATB2 gene in humans. Although interstitial deletions at 2q33 encompassing SATB2, either alone or contiguously with other genes, have been reported before, there is limited literature regarding intragenic mutations of this gene and the resulting phenotype. We describe five patients in whom whole exome sequencing identified five unique de novo mutations in the SATB2 gene (one splice site, one frameshift, and three nonsense mutations). The five patients had overlapping features that support the characteristic features of the SAS: intellectual disability with limited speech development and craniofacial abnormalities including cleft palate, dysmorphic features, and dental abnormalities. Furthermore, Patient 1 also had features not previously described that represent an expansion of the phenotype. Osteopenia was seen in two of the patients, suggesting that this finding could be added to the list of distinctive findings. We provide supporting evidence that analysis for deletions or point mutations in SATB2 should be considered in children with intellectual disability and severely impaired speech, cleft or high palate, teeth abnormalities, and osteopenia. © 2015 Wiley Periodicals, Inc.